2013
DOI: 10.1152/ajplung.00212.2013
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ion transport by oxidants

Abstract: Ion channels perform a variety of cellular functions in lung epithelia. Oxidant- and antioxidant-mediated mechanisms (that is, redox regulation) of ion channels are areas of intense research. Significant progress has been made in our understanding of redox regulation of ion channels since the last Experimental Biology report in 2003. Advancements include: 1) identification of nonphagocytic NADPH oxidases as sources of regulated reactive species (RS) production in epithelia, 2) an understanding that excessive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 98 publications
0
14
0
Order By: Relevance
“…Recently, PKC isoforms have been shown to phosphorylate the p47 phox subunit of Nox leading to assembly and activation. We, and others have recently shown that the seven Nox isoforms (Nox1-5, dual oxidase 1, and dual oxidase 2) are expressed in the human lung, albeit the cellular distribution of each Nox isoform in the human lung remains unclear (27). Importantly, we have shown that Nox2-derived reactive oxygen species (ROS) are critical regulators of lung ENaC activity (28,29).…”
mentioning
confidence: 85%
“…Recently, PKC isoforms have been shown to phosphorylate the p47 phox subunit of Nox leading to assembly and activation. We, and others have recently shown that the seven Nox isoforms (Nox1-5, dual oxidase 1, and dual oxidase 2) are expressed in the human lung, albeit the cellular distribution of each Nox isoform in the human lung remains unclear (27). Importantly, we have shown that Nox2-derived reactive oxygen species (ROS) are critical regulators of lung ENaC activity (28,29).…”
mentioning
confidence: 85%
“…More precisely, CS-induced oxidative stress has been correlated with the disruption of selective ion channels within the lung epithelium (33,95). These ion channels are vital for certain cellular processes and when obstructed, may markedly enhance chronic lung inflammation.…”
Section: Key Studies and Recent Advances: A Literature Review From 20mentioning
confidence: 99%
“…Specifically, the hindrance of a chloride and bicarbonate channel associated with the cystic fibrosis transmembrane conductance regulator (CFTR) gene is associated with difficulties in mucus transport, poor airway hydration, and disease susceptibility in COPD (95). Furthermore, ROS may interfere with the oxidative regulation of amiloride-and ROS-sensitive epithelial sodium channels (ENaC), responsible for the reabsorption of sodium and water (33). ENaC activity is regulated by the production of NOX, which is the rate-limiting factor in edema resolution in the lung; any ROS-induced inhibition of ion channel activity may drastically impede fluid clearance, heighten the inflammatory response, and disrupt the endothelial cell barrier (33).…”
Section: Key Studies and Recent Advances: A Literature Review From 20mentioning
confidence: 99%
See 1 more Smart Citation
“…Again I refer the readers to the Physiology in Medicine review by Dr. Chatterjee (7) as well as a comprehensive review on the role of NAPDH in the regulation of lung amiloride-sensitive epithelial sodium channels (13). On this topic, Sharma et al (49) showed that activation of ATII cell NADPH during ischemiareperfusion injury leads to the production of CXCL1, which contributes to the recruitment and activation of neutrophils and lung injury.…”
Section: Our Publishing Philosophymentioning
confidence: 99%